2014
DOI: 10.1007/s11892-014-0552-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Components in the Pathogenesis of Type 1 Diabetes

Abstract: Type 1 diabetes (T1D) results from progressive immune cell-mediated destruction of pancreatic β cells. As immune cells migrate into the islets they pass through the extracellular matrix (ECM). This ECM is composed of different macromolecules localized to different compartments within and surrounding islets; however, the involvement of this ECM in the development of human T1D is not well understood. Here we summarize our recent findings from human and mouse studies illustrating how specific components of the is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 97 publications
1
72
0
Order By: Relevance
“…Hence, while there was no overt remodelling, such as increased collagen deposition and large changes in wall thickness (Mulvany, 1999), there were changes to the vessel dimensions to accommodate their inability to respond appropriately to changes in flow, as reported in other mice models (Albinsson et al , 2007). There are reports of altered shear response in resistance arteries of diabetic and hypertensive rats (Matrougui et al , 1998; Bouvet et al , 2007; Belin de Chantemele et al , 2009; Vessieres et al , 2012; Dumont et al , 2014) where expression or glycosylation state of extracellular matrix molecules is commonly affected (Intengan & Schiffrin, 2000; Rauch et al , 2011; Bogdani et al , 2014). However, there has been no investigation of whether changes in shear response in such pathological vessels are associated with changes in laminin isoform expression, a possibility that requires future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, while there was no overt remodelling, such as increased collagen deposition and large changes in wall thickness (Mulvany, 1999), there were changes to the vessel dimensions to accommodate their inability to respond appropriately to changes in flow, as reported in other mice models (Albinsson et al , 2007). There are reports of altered shear response in resistance arteries of diabetic and hypertensive rats (Matrougui et al , 1998; Bouvet et al , 2007; Belin de Chantemele et al , 2009; Vessieres et al , 2012; Dumont et al , 2014) where expression or glycosylation state of extracellular matrix molecules is commonly affected (Intengan & Schiffrin, 2000; Rauch et al , 2011; Bogdani et al , 2014). However, there has been no investigation of whether changes in shear response in such pathological vessels are associated with changes in laminin isoform expression, a possibility that requires future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Collective changes in the structural complexes of ECM components are proposed to create a proinflammatory microenvironment that regulates crucial steps in the pathogenic process of type 1 diabetes such as immune cell adhesion and migration, immune cell activation, and b-cell death. The JDRF Network for Pancreatic Organ Donors with Diabetes (nPOD) ECM working group composed of three research teams (72) has initiated studies that will lead to our better understanding of the collective changes in the ECM that take place in human islets and lymphoid tissues during development of type 1 diabetes. Understanding the contribution of the ECM in type 1 diabetes could complete the "unfinished harmony" of the pathogenic process of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of abnormal DC and macrophages in fibronectin-containing peri-islet areas and in association with altered islet morphology early in life, during the period of rodent endocrine pancreas remodeling (65,68,69), suggested that functionally impaired macrophages and DC and altered islet ECM impact islet morphology and may be involved in the generation and/or progression of the autoimmune response in NOD mice (70). Recent systematic studies in human diabetic pancreata have implicated other specific ECM components in the regulation of leukocyte trafficking (20,71,72). These studies suggest that ECM components impact b-cell function and survival, and thus contribute to b-cell damage in diabetes (58,72).…”
Section: Islet Ecm In Type 1 Diabetesmentioning
confidence: 99%
“…Studies are now pointing to the role of the extracellular matrix (ECM) as a potential barricade to unwanted cellular immigrants [50]. Bogdani et al [23 & ] showed that there were elevated levels of hyaluronan and hyaluronan-binding proteins, called hyaladherins, within and around islets from donors with less than 10 years of T1D.…”
Section: Obstacles To Infiltrationmentioning
confidence: 99%